Design of sliding mode control for quadruple-tank MIMO process with time delay compensation. (April 2019) - Shah, D.H.; Patel, D.M.
Highlights: Robust control strategy for quadruple-tank MIMO process with delay compensation. Process delays in the system are compensated using Pade Approximation technique. Strategy offers faster convergence and negligible chattering in system variables. Closed-loop stability of MIMO system is derived using Lyapunov approach. The efficacy of proposed strategy is validated through simulation results. Abstract: In industrial applications, process delay and disturbance are considered to be major concerns which are responsible for the deterioration in the performance of multivariable systems. quadruple tank process (QTP) is one of the multivariable system that requires control over at least two variables. This paper deals with the designing of robust control strategy for quadruple-tank MIMO process with time delay compensation in the presence of matched uncertainty and process delays. The Sliding Mode Control (SMC) is designed for the class of non-linear MIMO system. The process delays in the system are compensated using Pade Approximation technique. The sliding mode control law is derived using non-switching reaching law which provides faster convergence speed for states and negligible chattering at the control signal. The sufficient condition for closed-loop stability of MIMO system is derived using Lyapunov approach. Simulation study focuses on a MIMO quadruple-tank process having process delays and matched disturbances. Simulation results are presented and compared with conventional quadruple tank process having process delays and power-rate reaching law to show the effectiveness of time delay compensation and robustness of proposed control algorithm derived using non-switching type reaching law in the presence of matched uncertainties and process delays.